Addressing the Need for Sexual, Mental, and Physical Healthcare in San Antonio’s Underinsured Lesbian, Gay, Bisexual, Transgender, and Queer Population - Donald Egan; Jelina Marie Castillo; Stacy Nguyen; Claude Hardy; Jessica Hill; Cassandra Jones; Delaney Rawson (Journal of Student-Run Clinics, 2021)
Background: In 2014, students from the University of Texas Health San Antonio Long School of Medicine conducted a community assessment of lesbian, gay, bisexual, transgender, and queer (LGBTQ+) healthcare needs. Participants reported low levels of sexually-transmitted infection (STI) screening, incomplete reporting of sexual history, and a desire for LGBTQ+-friendly physicians. As a result, a student-run free clinic, the Pride Community Clinic (PCC), was established. The PCC provides STI testing, mental health counseling, hormone replacement therapy (HRT), discounted medications, pre-exposure prophylaxis, human immunodeficiency (HIV) testing, and Pap smears. The purpose of this study is to analyze the demographics of the population treated at the PCC and the resources used to inform future developments within the clinic.Methods: PCC patient records were analyzed, and quantitative analysis was conducted with Microsoft Excel. The qualitative analysis was performed using notes written by medical students, attending physicians, and mental health providers.Results: The average age of patients (n=44) was 22 years, with a standard deviation of 10 years. Of the patients, 52% were racial minorities, and 50% lived below the poverty line. 84% identified as transgender and 68% a sexual minority. Additionally, 84% did not have a primary care provider, and 89% did not have insurance. HIV, gonorrhea, chlamydia, hepatitis C, and syphilis education were the most common screenings done. A review of medical notes found themes of transgender exploration, problems with healthcare access, and the utilization of counseling and preventative care.Conclusions: The PCC offers low-cost care for the underserved LGBTQ+ population in San Antonio. HRT is a common reason for visits, but patients also utilize STI testing and mental health services. The clinic has provided a valuable opportunity for students not only to gain general clinical experience but also to learn about the unique needs of LGBTQ+ patients.